2015
DOI: 10.1016/j.marchem.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic characterization of oceanic dissolved organic matter isolated by reverse osmosis coupled with electrodialysis

Abstract: a b s t r a c tOceanic dissolved organic matter (DOM) is one of the largest pools of reduced carbon on Earth, yet DOM remains poorly chemically characterized. Studies to determine the chemical nature of oceanic DOM have been impeded by the lack of efficient and non-fractioning methods to recover oceanic DOM. Here, a DOM fraction (~40 to 86% recovery) was isolated using reverse osmosis/electrodialysis (RO/ED) and analyzed by solid-state 13 C nuclear magnetic resonance (NMR) spectroscopy. Samples were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 90 publications
(148 reference statements)
3
21
0
Order By: Relevance
“…Differences between HMW-and SPE-DOM are less obvious for deep-sea DOM (Hertkorn et al, 2006(Hertkorn et al, , 2013, consistent with the semi-labile nature of APS/HPS. Relative to ultrafiltration and SPE, RO/ED has been reported to recover a larger and more representative fraction of total DOM (Vetter et al, 2007;Gurtler et al, 2008;Koprivnjak et al, 2009;Green et al, 2014;Helms et al, 2015), but the large sample volume requirement makes RO/ED unsuitable for the study of DOM in pore waters. A mini-electrodialysis system designed to handle small-volume samples has been developed, but appears to cause considerable DOC contamination (Chen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Differences between HMW-and SPE-DOM are less obvious for deep-sea DOM (Hertkorn et al, 2006(Hertkorn et al, , 2013, consistent with the semi-labile nature of APS/HPS. Relative to ultrafiltration and SPE, RO/ED has been reported to recover a larger and more representative fraction of total DOM (Vetter et al, 2007;Gurtler et al, 2008;Koprivnjak et al, 2009;Green et al, 2014;Helms et al, 2015), but the large sample volume requirement makes RO/ED unsuitable for the study of DOM in pore waters. A mini-electrodialysis system designed to handle small-volume samples has been developed, but appears to cause considerable DOC contamination (Chen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Combined neutral sugar distributions of semi-labile DOM and foam are also similar (Gogou and Repeta, 2010). 1 H NMR and 13 C NMR spectra of DOM collected by ultrafiltration, SPE, and ED/RO all show resonances assigned to semi-labile DOM carbohydrate as deep as 5200 m, but further chemical and isotopic characterization is needed to link surface and deep reservoirs of semi-labile DOM (Benner et al, 1992;Helms et al, 2013;Quan and Repeta, 2007;Sannigrahi et al, 2005).…”
Section: B Composition and The Cycling Of Semi-labile Dommentioning
confidence: 96%
“…The processes that lead to the formation and removal of SPE-DOM in the ocean are not known, but high-field NMR and high-resolution MS have added unprecedented detail to our knowledge of its composition (Dittmar and Koch, 2006;Helms et al, 2013;Hertkorn et al, 2006Hertkorn et al, , 2012. 1 H NMR spectra are characterized by broad peaks between 0.8 and 10 ppm with substantial signal overlap (Figure 2.10).…”
Section: Characterization Of Spe-dom By High-field Nmrmentioning
confidence: 99%
“…Few studies have reported spectral slope from 350 to 550 nm to our knowledge (Hancke et al, 2014;Kowalczuk et al, 2006), making it difficult to directly assess what S G350:550 estimates about CDOM composition. We propose that S E350:400 is a better metric for tracking compositional changes in the CDOM pool affiliated with photodegradation and in situ production of CDOM as suggested by Helms et al (2015Helms et al ( , 2013. However, S G350:550 displayed greater uniqueness between provinces, while S E350:400 displayed more consistent trends with depth across all spectral ranges.…”
Section: 1002/2017gb005756mentioning
confidence: 90%